Reflexiones en torno al acceso al agua en el Perú, en el marco de la nueva Ley de Recursos Hídricos - Ruiz Ostoic, Lucía (2013)
The difficulty involved addressing issues related with water management in Peru is the article’s starting point. Therefore, the water issue approach is introduced explaining its administrative procedures, the rights involved and making a critical analysis of 2008 Water Resources Law. Finally, the need for an integrated management analysis of the water resource is highlighted by integrally understanding the General Water Law as well as the current Water Resources Law, and encouraging dialogue among social actors involved in order to avoid future conflicts.